Variation of pediatric and adolescents head and neck pathology in the city of Jeddah: A retrospective analysis over 10 years - Ahmed O. Al Yamani; Maisa O. Al Sebaei; Lojain J. Bassyoni; Alaa J. Badghaish; Hussam H. Shawly (Saudi Dental Journal)
This study was conducted to present a comprehensive view of the most common head and neck pathologies among the pediatric and adolescent population of the city of Jeddah, Saudi Arabia. Data were collected from the oral and maxillofacial surgery (OMFS) records at King Abdulaziz University Hospital and King Fahad Hospital Jeddah (KFHJ) from the period 1998 to 2009. All patients who were 18 years of age and younger were included in the study. Identified lesions were classified into four categories: cystic, neoplastic, vascular and fibro-osseous. Age and sex distribution of the lesions were also calculated. A total of 155 patients were included in this study. Of all the lesions, 143 (92.26%) were benign and 12 (7.74%) were malignant; 63 (40.65%) were cysts; 48 (30.97%) were neoplasms; 23 (14.84%) were vascular and 21 (13.55%) were fibro-osseous tumors. The most common lesions were hemangioma (20 cases; 12.9%) followed by retention cyst (19 cases; 12.26%) and dentigerous cyst (15 cases; 9.68%). The most common benign odontogenic neoplasm was odontoma (7 cases; 4.52%), of which central giant cell granuloma (6 cases; 3.87%) was the most frequent benign nonodontogenic tumor and lymphoma (6 cases; 3.87%) was the most common malignant one. Although this study might benefit clinicians in guiding them through differential diagnosis of pediatric and adolescent head and neck pathology in reference to their sex and age groups, governmental efforts are badly needed to establish a Saudi childhood pathology registry. Keywords: Adolescents head and neck pathology, Pediatric head and neck pathology, Ameloblastoma in Saudi children, Lymphoma in Saudi children